Collagen‐Derived N‐Acetylated Proline‐Glycine‐Proline in Intervertebral Discs Modulates CXCR1/2 Expression and Activation in Cartilage Endplate Stem Cells to Induce Migration and Differentiation Toward a Pro‐Inflammatory Phenotype. (December 2015) - Feng, Chencheng; Zhang, Yang; Yang, Minghui; Huang, Bo; Zhou, Yue
Abstract : The factors that regulate the migration and differentiation of cartilage endplate stem cells (CESCs) remain unknown. N ‐Acetylated proline‐glycine‐proline ( N ‐Ac‐PGP) is a chemokine that is involved in inflammatory diseases. The purpose of this study was to detect N ‐Ac‐PGP in degenerative intervertebral discs (IVDs) and to determine its roles in the migration and differentiation of CESCs. Enzyme‐linked immunosorbent assay (ELISA) and liquid chromatography‐mass spectrometry results indicated that the levels of the proteases that generate N ‐Ac‐PGP as well as N ‐Ac‐PGP levels themselves increase with the progression of IVD degeneration. Immunohistochemistry and an N ‐Ac‐PGP generation assay demonstrated that nucleus pulposus (NP) cells generate N ‐Ac‐PGP from collagen. The effects of N ‐Ac‐PGP on the migration and differentiation of CESCs were determined using migration assays, RT‐PCR, immunoblot analysis, and ELISA. The results showed that the expression of N ‐Ac‐PGP receptors (CXCR1 and CXCR2) in CESCs was upregulated by N ‐Ac‐PGP. Additionally, N ‐Ac‐PGP induced F‐actin cytoskeletal rearrangement in CESCs and increased CESC chemotaxis. Furthermore, N ‐Ac‐PGP recruited chondrocytes and spindle‐shaped cells from the cartilage endplate (CEP) into the NP in vivo. These spindle‐shaped cells expressed CD105 and Stro‐1 (mesenchymal stem cell markers). N ‐Ac‐PGP induced the differentiation of CESCs toward a pro‐inflammatory phenotype with increased production of inflammatory cytokines rather than toward an NP‐like phenotype. Our study indicated that, in the complex microenvironment of a degenerative disc, N ‐Ac‐PGP is generated by NP cells and induces the migration of CESCs from the CEP into the NP. N ‐Ac‐PGP induces a pro‐inflammatory phenotype in CESCs, and these cells promote the inflammatory response in degenerative discs. Stem Cells 2015;33:3558–3568